Gene therapy for inherited retinal diseases: exploiting new tools in genome editing and nanotechnology - Carvalho, Cláudia; Lemos, Luísa; Antas, Pedro; Seabra, Miguel C. (Frontiers in Ophthalmology, 2023)
Inherited retinal diseases (IRDs) encompass a diverse group of genetic disorders that lead to progressive visual impairment and blindness. Over the years, considerable strides have been made in understanding the underlying molecular mechanisms of IRDs, laying the foundation for novel therapeutic interventions. Gene therapy has emerged as a compelling approach for treating IRDs, with notable advancements achieved through targeted gene augmentation. However, several setbacks and limitations persist, hindering the widespread clinical success of gene therapy for IRDs. One promising avenue of research is the development of new genome editing tools. Cutting-edge technologies such as CRISPR-Cas9 nucleases, base editing and prime editing provide unprecedented precision and efficiency in targeted gene manipulation, offering the potential to overcome existing challenges in gene therapy for IRDs. Furthermore, traditional gene therapy encounters a significant challenge due to immune responses to viral vectors, which remain crucial obstacles in achieving long-lasting therapeutic effects. Nanotechnology has emerged as a valuable ally in the quest to optimize gene therapy outcomes for ocular diseases. Nanoparticles engineered with nanoscale precision offer improved gene delivery to specific retinal cells, allowing for enhanced targeting and reduced immunogenicity. In this review, we discuss recent advancements in gene therapy for IRDs and explore the setbacks that have been encountered in clinical trials. We highlight the technological advances in genome editing for the treatment of IRDs and how integrating nanotechnology into gene delivery strategies could enhance the safety and efficacy of gene therapy, ultimately offering hope for patients with IRDs and potentially paving the way for similar advancements in other ocular disorders.